Technology Transfer, International Law And Protection of Marine Biodiversity Beyond National Jurisdiction: Key Issues for a New International Agreement - Jorge Antonio Quindimil López (Paix et Sécurité Internationales, 2020)
This paper deals with the relevant issues on technology transfer arising from the process of negotiation of a new international legally binding instrument on marine biodiversity in areas beyond national jurisdiction. From the difficult implementation of provisions contained in the United Nations Convention on the Law of the Sea and other international instruments, to the current state of negotiations in the Intergovernmental Conference on Marine Biodiversity of Areas Beyond National Jurisdiction, this paper tries to present the challenges, the gaps and the opportunities at stake. This is a historic opportunity to shape integral and specific protection of the biological diversity beyond national jurisdiction, while the oceans are facing more threats and perils than never.